The Irony of Accountability: How a Performance-Inducing Policy Reduces Motivation to Perform - Trinidad, Jose Eos R (Archīum Ateneo, 2023)
Although sociological and organizational studies have focused on the influence of quantification on behavior, the author focuses on quantification’s increasingly important consequences on well-being and motivation. Using the case of U.S. education, which has long relied on accountability policies, the author finds that attendance at schools with high-stakes accountability predicted lower student self-efficacy, that is, decreased task motivation and resilience as well as increased fear of failure—salient for low-income, urban, and public schools. These associations, however, did not spill over to social and life satisfaction dimensions of well-being. Taken together, these findings suggest the irony of accountability, where data used to induce performance may unintentionally reduce people’s motivation to perform, particularly consequential in disadvantaged contexts. This article is an attempt to contribute to a broader theorization of quantification, affecting not only external behaviors and organizational structures but also internal personal dispositions. Finally, the article provides implications for the study of well-being, organizations, and education policy.